Indonesia's Role In Conflict Resolution In Afghanistan Through Soft Power - Fajar Hermansyah; Rachman , Arif; Halkis, Mhd. (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
This research focuses on Indonesia's role in resolving the conflict in Afghanistan through soft power, specifically through cultural and religious equality approaches. The study highlights that the conflict in Afghanistan has had a negative impact on the country's development and stability. Indonesia's special attitude towards foreign policy activities involving Muslim countries is influenced by its large Muslim population and ties with other Muslim countries. The study utilizes qualitative methods, specifically a descriptive-analytic approach, to analyze the subject matter. The research subjects range from books, documents, regulations, meeting minutes, diaries, and historical artifacts. The findings indicate that Indonesia's soft power approach through cultural diversity and tolerance, as well as religious similarity, have contributed to its role as a mediator in the Afghan conflict. The research highlights the Indonesian government's efforts as well as the involvement of Afghan people in Indonesia and moderate Islamic organizations such as the Nahdlatul Ulama and Muhammadiyah. Overall, this study sheds light on Indonesia's significant role in resolving the conflict in Afghanistan through soft power approaches.